7 - Diaspora Collaboration and Knowledge Production in Africa: Reflections on Caveats and Opportunities - Fongwa, Samuel (Journal of Higher Education in Africa, 2022)
Irrespective of its conceptualisation, diaspora contributes to the development of the homelands through diverse forms of collaboration. The increase in remittances and diaspora involvement in fostering democratic values are obvious examples. A new emphasis, however, is on developing the African academia through various forms of partnership and collaboration between diaspora-based and African-based academics. A number of initiatives, funding opportunities and research partnerships to this effect are emerging. Nevertheless, these partnerships are complex and do not always translate into win-win situations, especially for institutions and academics in the global South. In this article, I reflect on some personal experiences in research collaborations as part of the diaspora and as an African-based academic. In so doing, three possible caveats in maximising the gains of diaspora partnerships in knowledge production are highlighted. I argue that while opportunities for knowledge collaboration abound, ensuring a sustainable win-win relationship in diaspora partnerships demands careful introspection at every turn.